Empowerment Seaweed Farmers to Improve Community Welfare in Seriwe Village, Jerowaru District from a Shariah Economic Perspective - Ahmad Rezi Fauzia; Asep Jajang Karma Sanjaya; Muh. Salahuddin (STKIP Taman Siswa Bima, 2025)
This study aims to analyze the implementation of Islamic economic principles in the empowerment of seaweed farmers and its impact on improving the welfare of the community in Seriwe Village, Jerowaru District, East Lombok Regency. The village has been designated as one of the seaweed production centers in West Nusa Tenggara; however, it continues to face challenges such as limited access to capital, inadequate technology, and weak farmer institutions. This research employs a descriptive qualitative method, using data collection techniques such as direct observation, in-depth interviews, and documentation with key informants, including farmers, village officials, and the Department of Marine Affairs and Fisheries. The results indicate that empowerment efforts have so far been limited to the formation of farmer groups and the provision of production tools, without sustainable training or business assistance. Nevertheless, some Islamic economic principles such as justice, mutual cooperation (ta’awun), consultation (shura), and blessings in economic activity have started to emerge in the interaction patterns and business practices of the farmers interction patterns had positive effects, including increased income for some farmers, improved social cohesion, and emerging self-reliance in developing seaweed businesses. This research concludes that the application of Islamic economic principles in empowering seaweed farmers has the potential to enhance community welfare. However, further involvement is required from government bodies and related institutions to strengthen farmer organizations, expand access to Islamic financing, and provide continuous business development support to ensure sustainable community empowerment in coastal areas.